Time trends in risk factor control and use of secondary preventive medication among patients with myocardial infarction attending cardiac rehabilitation: data from the SWEDEHEART registry 2006–2017. (25th November 2020) - Leosdottir, M; Hagstrom, E; Hadziosmanovic, N; Norhammar, A; Lindahl, B; Hambraeus, K; Jernberg, T; Back, M
Abstract: Background: Systematically monitoring results within cardiac rehabilitation (CR) has been highlighted as a possible way to improve CR outcomes. The nationwide SWEDEHEART registry has monitored quality of care post myocardial infarction (MI) in Sweden since the 1990s. Follow-up data describing treatment and outcomes within CR has been collected since 2006. Purpose: To describe changes in risk factor control and use of secondary preventive medication for post MI patients after completion of CR in Sweden 2006–2017, and to compare with trends in the EUROASPIRE surveys. Methods: All patients who suffered an MI and attended a one-year CR follow-up visit registered in SWEDEHEART 2006–2017 were included (n=66 666, 18–74 years, 75% men). Trends in risk factor control and secondary preventive medication were collected yearly and analyzed over the time period using Cochran-Armitage trend test. Comparisons were made to data from the EUROASPIRE III (2006–2007), IV (2012–2013) and V (2016–2017) surveys, where patients with coronary artery events or interventions were interviewed at approximately 1.2 years after the index event (n=25 225, 18–80 years, 74% men). Results: Trends in blood pressure (BP) and low-density lipoprotein cholesterol (LDL-C) control, smoking, and central obesity are shown in the Figure. The proportion of patients achieving BP goal <140/90 mmHg and LDL-C goal <1.8 mmol/L increased by 16% and 29% from 2006 to 2017 in SWEDEHEART (p for trend <0.0001 for both), compared to 14% and 8% between EUROASPIRE III and V. Of patients who were active smokers at the time of the index event, the proportion still smoking at one-year remained unchanged in SWEDEHEART (43% in 2006 and 2017) while increasing from 52% to 55% in the EUROASPIRE surveys. An increase in prevalence of central obesity from approximately 50% to 60% was observed in both cohorts. The proportion of patients with obesity (BMI ≥30kg/m 2 ) and diabetes increased in SWEDEHEART during the observed period from 23% to 29% (obesity) and 18% to 25% (diabetes) (p for trend <0.0001 for both). The proportions in 2017 were considerably lower than in EUROASPIRE V (2016–2017), where 38% were obese and 29% had diabetes. The use of statins increased from 89% to 93%, ezetimibe from 5% to 21%, and ACE/ARB from 65% to 82% in SWEDEHEART (p for trend <0.0001 for all). In comparison, in EUROASPIRE V the proportion treated with lipid lowering medication of any kind was 84% and with ACE/ARB was 75%. Conclusion: Between 2006–2017, considerable improvements were achieved in risk factor control and use of secondary preventive medication for MI patients completing CR in Sweden, where all patients were monitored through the SWEDEHEART registry. The improvements were larger than observed in the EUROASPIRE surveys during the same time period. Continuous and nationwide auditing of CR outcomes, as well as local review of performance, could be possible explanations for some of the observed differences. Funding Acknowledgement: Type of funding source: None